The Use of Capsule Endoscopy to Determine Tablet Disintegration In Vivo - Lasse I. Blaabjerg; Li Fan; Xiaoli Chen; Philip J. Sassene (MDPI AG, 2020)
The preferred delivery route for drugs targeted for systemic effect is by oral administration. Following oral administration, a solid dosage form must disintegrate and the drug dissolve, thereafter permeating the intestinal mucosa. Several different in vitro methods are used to investigate these processes, i.e., disintegration tests, dissolution tests, and permeability models. However, the actual behavior of oral dosage forms in the environment of the gastro-intestinal tract is not very well elucidated using these conventional methods. In this study, the use of capsule endoscopy to determine tablet disintegration in vivo was assessed. Panadol and Panadol Rapid (acetaminophen/paracetamol) were used as the test material. The in vivo tablet disintegration behavior in beagle dogs was assessed by the use of capsule endoscopy. The in vitro tablet disintegration behavior was assessed using the European Pharmacopeia (Ph. Eur.) disintegration test. The study showed that the in vivo disintegration times of Panadol and Panadol Rapid were 24.7 and 16.5 min, respectively, when determined by capsule endoscopy, which corresponded to the pharmacokinetic data. By contrast, the in vitro disintegration times of the same formulations were 5.5 and 4.0 min, respectively, when determined by the Ph. Eur. disintegration test. In conclusion, capsule endoscopy can be used to determine the in vivo tablet disintegration behavior. By contrast, the in vitro methods appear to not be predictive of the disintegration behavior in vivo but may be used to rank the order the formulations with respect to disintegration time.